Correct the mistake in each sentence
1. Buji Khalifa Tower is more high than Keangnam Tower
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
c \(\frac{\left(2x-4\right)\left(x-3\right)}{\left(x-2\right)\left(3x^2-27\right)}=\frac{2\left(x-2\right)\left(x-3\right)}{3\left(x-2\right)\left(x^2-9\right)}\)
\(=\frac{2\left(x-2\right)\left(x-3\right)}{3\left(x-2\right)\left(x-3\right)\left(x+3\right)}=\frac{2}{3\left(x+3\right)}\)
d, \(\frac{x^2+5x+6}{x^2+4x+4}=\frac{\left(x+2\right)\left(x+3\right)}{\left(x+2\right)^2}=\frac{x+3}{x+2}\)
Tương tự với a ; b
x^3 - x^2 - 7x + 3 x - 3 x^2 + 2x - 1 x^3 - 3x^2 2x^2 - 7x + 3 2x^2 - 6x -x + 3 -x + 3 0
Vậy \(\left(x^3-x^2-7x+3\right):\left(x-3\right)=x^2+2x-1\)
\(\left(2x+1\right)^2+\left(3x-1\right)^2+2\left(2x+1\right)\left(3x-1\right)\)
\(=\left(2x+1\right)^2+2\left(2x+1\right)\left(3x-1\right)+\left(3x-1\right)^2\)
\(=\left[\left(2x+1\right)+\left(3x-1\right)\right]^2=\left(2x+3x+1-1\right)^2=25x^2\)
\(\left(2x+1\right)^2+\left(3x-1\right)^2+2\left(2x+1\right)\)\(\left(3x-1\right)\)
\(=\left(2x+1\right)^2+2\times\left(2x+1\right)\left(3x-1\right)\)\(+\left(3x-1\right)^2\)
\(=\left[\left(2x+1\right)+\left(3x-1\right)\right]^2\)
\(=\left(2x+1+3x-1\right)^2\)
\(=\left(5x\right)^2\)
\(=25x^2\)
Học tốt ~!
\(\left(x+y\right)^2+\left(x-y\right)^2-2\left(x+y\right)\left(x-y\right)\)
\(=\left(x+y\right)^2-2\left(x+y\right)\left(x-y\right)+\left(x-y\right)^2\)
\(=\left[\left(x+y\right)-\left(x-y\right)\right]^2=\left(x+y-x+y\right)^2=4y^2\)
Correct the mistake in each sentence
1. Buji Khalifa Tower is more high than Keangnam Tower
\(\rightarrow\)Burj Khalifa tower is taller than Keangnam tower
Correct the mistake in each sentence
1. Buji Khalifa Tower is more high than Keangnam Tower
Buji Khalifa Tower is more higher than Keangnam Tower